ANALISIS PARTISIPASI TENAGA KERJA WANITA DAN KONTRIBUSI PENDAPATAN (Studi Kasus Agroindustri Patin Desa Koto Mesjid Kabupaten Kampar, Provinsi Riau) - Sri Ayu Kurniati (UIR Press, 2016)
Agricultural sector development implemented interrelated, complementary support, and with the industrial sector, namely through the development of area-based economic growth integrated aquaculture that is contained in the concept of Minapolitan in Kampar Regency. This research aims to: (1) analyze the magnitude of women's labor force participation rates, (2) analyze factors that affect women's labor force participation, and (3) analyze the contribution of women's labor income. The research method is the case study on the central processing of agro-industries fish the catfish the whole workforce is women in the village of Koto Mosque District XIII Koto Kampar in Kampar Regency. Respondents taken in the census on 8 people labor women and analyzed using quantitative descriptive analysis. The results showed that the number of family member, wage, education, age, total household income and spare time together affect the labor participation of women. Work participation rates (TPK) amounted to 1.05% meaning of 100 females age earning only 1 person working on catfish agro-industries. The magnitude of the contribution of women's labor income is 19,88% of the overall income of households.